Pengaruh Tingkat Penggenangan terhadap Pertumbuhan Semai Pedada (Sonneratia caseolaris (L.) Engler) di Kawasan Mangrove Tol Sedyatmo Angke Kapuk, Jakarta Utara - Yuda Purnama; Iwan Hilwan; Cecep Kusmana (Jurnal Silvikultur Tropika, 2012)
Influence of Inundation Level Toward The Growth of Pedada Seedling (Sonneratia caseolaris (L.) Engler) in Mangrove Area Tol Sedyatmo Angke Kapuk, North Jakarta.Global warming that causing the melting of iceberg in the pole have an impact on rising of level sea which impact on mangrove forest ecosystems. So that, we need to know the information about species of mangroves that can be adapted to increasing sea level and also species that can support for mangrove rehabilitation. Purpose of this research is to elaborate the effect of inundation on seedling growth and determine the level of inundation that support the good seedling growth. This research used randomized block design with inundation level as a treatment. There were three treatments consisting of inundation until the limit of the root neck, inundation between ¼ stem height and ½ stem height, and inundation between ½ stem height and ¾ stem height. Mangrove species that is used in this research is 2 and 4 months years old seedling of S. caseolaris. The research results showed that the level of inundation of the root neck gives the best effect to seedling growth. However, S. caseolaris can adapt and having good growth at inundation up to ½ stem height. In general, the influence of inundation level give effect to the growth variable responses, except in height, length of internode, and height increment of seedling.